Determining Passenger Satisfaction on Passenger Ships: An Analysis of Excellent Service, Punctuality, and Infrastructure - Alfais Amin Darmawan (Siber Nusantara Review & Yayasan Sinergi Inovasi Bersama (SIBER), 2025)
The purpose of this literature review is to develop hypotheses regarding the influence between variables that can be used for further research in the field of marketing management. The article “Literature Review of Passenger Satisfaction Determinants: Analysis of Excellent Service, Punctuality, and Infrastructure” is a scientific article in the field of marketing management. The approach used in this literature review is descriptive qualitative. The data collection technique involves conducting a literature review or reviewing relevant previous articles. The data used in this descriptive qualitative approach were obtained from previous studies relevant to this study and sourced from academic online media such as Thomson Reuters Journal, Springer, Taylor & Francis, Scopus Emerald, Elsevier, Sage, Web of Science, Sinta Journal, DOAJ, EBSCO, Google Scholar, and digital reference books. The results of this literature review article are as follows: 1) Excellent service influences passenger satisfaction on passenger ships; 2) Punctuality influences passenger satisfaction on passenger ships; and 3) Infrastructure influences passenger satisfaction on passenger ships.